Ovarian cancer stem cells: Critical roles in anti-tumor immunity - Ding, Jing; Zhang, Yan; Che, Yan (Frontiers in Genetics, 2022)
Ovarian cancer is a significant cause of cancer-related mortality in women. Over the past 3 decades, there has been a high incidence of recurrent chemoresistant disease, despite the relative effectiveness of current treatment strategies. This is partly attributed to cancer stem cells (CSC), a subpopulation that has acquired stem cell properties that allow these cells to evade standard chemotherapy and cause disease recurrence. Therefore, there is an urgent need for basic knowledge about CSC to develop innovative therapeutic approaches for ovarian cancer. These CSC subpopulations have been identified in ovarian cancer cell lines, tumors or ascites, and findings suggest that ovarian CSCs may be as heterogeneous as the disease itself. CSCs regulate the phenotype and function of immune cells involved in antitumor immunity, so a better understanding of the signaling pathways that interact between CSCs, immune cells and tumor cells will pave the way for the clinical application of CS in cancer immunotherapy. This review will focus on the markers currently used to identify and isolate these cells summarize current knowledge on the molecular and cellular mechanisms responsible for CSC-dependent regulation of antitumor immune responses. We will discuss the signaling pathways involved in CSC survival, replication, and differentiation as well as potential therapeutic targeting strategies.